PENGELOLAAN ANGKUTAN UMUM PERDESAAN PADA DINAS PERHUBUNGAN KABUPATEN SUMEDANG - Zia Nurazizah; Suherman; Lalas Sulastri; Dewi Maharani (JRPA - Journal of Regional Public Administration, 2025)
This research discusses the management of rural public transportation at the Sumedang Regency Transportation Office. Which is motivated by several main factors related to the needs of rural communities for adequate access to transportation with good quality. This study aims to understand the extent of rural public transport management in improving the quality of rural public transport services and identifying inhibiting factors and efforts made in the implementation of rural public transport management. The research method used was qualitative with descriptive analysis. Informants were determined using purposive sampling technique. Data collection techniques were carried out through literature studies, field studies (observation, interviews, and documentation) and triangulation. After that, validity techniques are credibility test, transferability test, depenability test, and confirmability test. Then for data processing using data collection, data reduction, data display, and conclusion drawing/verification. The results showed that the management of rural public transport involved various parties in planning, organizing, mobilizing, and monitoring. However, in its implementation, there are obstacles such as limited budget, lack of public interest in using rural public transport, and low awareness of transport entrepreneurs to rejuvenate their fleet. Efforts are made by providing subsidies and free feasibility tests for transportation entrepreneurs.